NUTRITIONAL VALUE OF THE PEANUT WORMS Siphonosoma australe australe (Keferstein, 1865) and Sipunculus nudus Linnaeus, 1766 (SIPUNCULUS: PHASCOLOSOMATIDAE) IN THE MANGROVE FOREST OF GIANH RIVER, QUANG BINH PROVINCE - Nguyễn Thị, Hường Mỹ; Chứng, Ngô Đắc (Hue University Journal of Science: Natural Science, 2019)
Siphonosoma australe australe (Keferstein, 1865) and Sipunculus nudus Linnaeus, 1766 are two species and subspecies of peanut worms belong to phylum Sipuncula were re-ported in the mangrove forest of the Gianh river, Quang Binh province. Study on nutritional composition of peanut worm to give a great learning on their value in order to breed and develop reasonability and sustainability this resource. Peanut worms collected from 10 sites on year 2015 were analysed total protein by methods AOAC (Association of Official Analytical Chemists) and content of amino acid by method HPLC (High-performance liquid chromatography). Results indicate that average content of total protein 11% (Siphonosoma australe australe) and 9,79% (Sipunculus nudus). Specially, 19 amino acids (9 essential amino acids) were found in nutritional composition of meat. In addition, a great of mineral content ((7,02% in Siphonosoma australe australe and 16,87% in Sipunculus nudus) and lipid content 0,84% và 1,30% in turn.